TEACHER’S STRATEGIES IN TEACHING READING COMPREHENSION DESCRIPTIVE TEXT AT TENTH GRADE STUDENTS OF SMA ST. THOMAS 2 MEDAN - Gabriela Elisabeth Sibagariang; Marisi Debora (Universitas Negeri Medan, 2023)
The purposes of this study analyzed kind of strategies used by English teachers at SMA St. Thomas 2 Medan in teaching reading comprehension descriptive text, and analyzed how the English teacher used semantic mapping in teaching reading comprehension descriptive text. This research was conducted by descriptive qualitative method. The participants of this research were an English teacher of grade 10 at SMA St. Thomas 2 Medan and the students of class X IPS 1 SMA St. Thomas 2 Medan. The data from this research were the results of observations and interviews. The researcher also asked the teacher what strategies the teacher usually uses in teaching reading comprehension, especially in descriptive texts. The teacher replied that she had three different teaching strategies for teaching reading comprehension. The three strategies are: Mind Mapping/Semantic Mapping, Reciprocal Teaching, and Question Answer Relationship (QARs). Based on the results of observations that had been made by researchers, teachers carried out learning activities using teaching strategies properly and there were no obstacles.